Political Polarization and Interest Groups - Cognata, Dominick (CSUCI Journal of Undergraduate Research, 2014)
Recently the US Congress has gotten lost on the road to consensus. The 113th Congress is onpace to be the least productive in American history. Just last fall the nation saw the federal government’sauthority to spend money temporarily suspended in an attempt to force a repeal of the Affordable Careand Patient Protection Act, also known as Obamacare. The differences between Democrats andRepublicans once seemed subtle to many Americans, but this has changed, and our current politicalenvironment is all the more tense because of this. In short, the area where these competing visions forthe country once converged has collapsed, leaving few opportunities for compromise between liberalsand conservatives. This is the space we refer to as the “political center.”